Application of environmental performance analysis for urban design with Computational Fluid Dynamics (CFD) and EcoTect tools: the case of Cao Fei Dian eco-city, China - Cheshmehzangi, Ali; Zhu, Yan; Li, Bo (Elsevier, 2017)
This paper suggests a type of quantitative research method with the application of Computational Fluid Dynamics (CFD) and EcoTect tools for a sustainable urban design project. This paper is part of a funded research study and was completed in 2010. This study is part of the larger project for planning and development of Cao Fei Dian eco-city development in North-Eastern China; one of the first eco-city development projects in the first batch of pilot eco-cities in China. The research programme addresses the main aspects of good practice in terms of eco-design and sustainability. These aspects include wind flow analysis around buildings, insolation analysis of open spaces, pollutant dispersion in water systems and noise control on urban highways. This study aims to explore a range of research methods in order to enhance the performance of integrated design with a comprehensive planning stage. The integration in evaluation across professions and subject boundaries is emphasised to identify the key gaps between sustainability and design. The main method of this study is the application of CFD and EcoTect tools for environmental performance of a larger urban area than the common use for architectural interventions or immediate outdoor spaces of a project. This study suggests an integrated urban design model with the application of computational tools (i.e. CFD and EcoTect in here) and how these could inform, from a technical dimension, a more comprehensive approach to executing best practice in design and planning. The paper concludes by suggesting an integrated model of urban design to achieve urban sustainability.